PENGARUH KOMITMEN PROFESI TERHADAP TURNOVER INTENTIONS DENGAN KEPUASAN KERJA SEBAGAI VARIABEL PEMEDIASI (Studi pada Karyawan Kantor Konsultan Pajak Di Semarang) - Rachmawati Rachmawati Meita Oktaviani; Ida Nurhayati (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2014)
This study aims to examine and analyze job satisfaction as a mediator variable between the relationship between theprofession's commitment to intentions turnover.The population used in this study are the employees who work at the Officeof Tax Consultants in Semarang. The sampling technique used was judgment sampling, the number of samples selectedstudies say as many as 54. Result of this research, professional commitment and job satisfaction partially no effect onturnover intentions. Profession's commitment in this study only had an influence on job satisfaction. The conclusion of thisstudy job satisfaction variable cann’t be mediator variable between the profession's commitment to turnover intentions.Keywords: Profession's Commitment, Job Satisfaction, Turnover Intentions